PEMAHAMAN TREND FASHION SISWA KELAS XI TATA BUSANA DI SEKOLAH MENENGAH KEJURUAN - Chintya Safitri (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2017)
The purpose of research is to determine the level of understanding of fashion trends of students of fashion class XI SMK Karya Rini Yogyakarta. The type of research is descriptive. Technique of collecting data using questionnaire method. The results showed the understanding of Fashion Trend students in sufficient categories with a relative frequency of 47.06%. The ability of students to translate into the category sufficient, with the relative frequency of 58.83%, it’s meaning that students have the ability to translate a good enough, Ability to interpretation included to the low category with a relative frequency of 47.05%. Students have a poor ability to interpret fashion trends; And the ability to extrapolate is included in sufficient categories with a relative frequency of 44.12%. The ability of students to see what is predicted in the fashion trend is quite good. Key words: Understanding, Trend Fashion